The importance of transference in the therapeutic process for psychoanalysis: A literature review (Research, Society and Development, 2024)
This article addresses the importance of transference in the therapeutic process within Psychoanalysis, focusing on understanding this phenomenon as an essential element for the development of psychoanalytic treatment. Transference is understood as the process by which the patient projects feelings, desires and past experiences onto the analyst, especially those linked to significant figures from his/her childhood. This phenomenon plays a crucial role in the dynamics of therapy, as it allows access to the patient's unconscious and facilitates the elaboration of internal conflicts. The objective of this article is to present a study of the main theories and contributions of Freud, Lacan and other psychoanalysts on transference, in addition to discussing their implications for treatment, their challenges and the importance of managing the analyst through a literature review. The text also explores the relationship between transference and countertransference, two aspects that interact deeply and that need to be worked on carefully for the therapeutic process to be successful. The review also highlights how transference can be seen as a healing instrument, enabling the reconfiguration of old emotional and behavioral patterns. Finally, it is argued that transference is one of the key elements in psychoanalytic treatment, being fundamental for the realization of interpretations and the advancement of the therapeutic process.